Presenteeism and mental health of workers during the COVID-19 pandemic: a systematic review - García-Iglesias, Juan Jesús; Gómez-Salgado, Juan; Apostolo, Joao; Rodrigues, Rogério; Costa, Emília Isabel; Ruiz-Frutos, Carlos; Martínez-Isasi, Santiago; Fernández-García, Daniel; Vilches-Arenas, Ángel (Frontiers in Public Health, 2023)
Background: A large number of workers attend work despite being ill. Attending work during sickness can have a number of consequences for the worker (e.g. worsening of physical and mental condition), for co-workers, and for the company, and for service users.The aim of this study was to assess the factors influencing presenteeism and mental health of workers during the COVID-19 pandemic.Methods: A systematic review following the PRISMA format was conducted in the Pubmed, Scopus, Web of Science (WoS), Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycInfo, and ScienceDirect electronic databases in January 2023, using the following key words: Presenteeism, Mental Health, and COVID-19. The eligibility criteria applied were original articles published in English, Spanish, French, German, and Portuguese, workers during the COVID-19 pandemic (data collection date: 01/01/2020 -01/01/2023), and articles assessing at least one measure of presenteeism and mental health status. Methodological quality was assessed using the critical appraisal tools of the Joanna Briggs Institute. The followed protocol is listed in the International Prospective Register of Systematic Reviews (PROSPERO) with code CRD42023391409 Results: A total of 25 studies were included in this review recruiting a total of 164,274 participants.